DOI: 10.47749/t/unicamp.2012.866595
|View full text |Cite
|
Sign up to set email alerts
|

O discurso narrativo nas afasias

Abstract: Minha profunda gratidãoA toda minha amada família, pelo amor incondicional, inspiração, confiança, força e compreensão.À minha irmã e amiga de todas as horas, Rosana. Aos meus pais e aoPedro, pelo exemplo de honestidade, preocupação e respeito para com o outro. A todos os antigos e novos amigos. que tive a bênção de conhecer em minha jornada. À minha orientadora, Profa. Rosana, pela paciência, comprometimento, exemplo de ética, respeito, humildade e prazer com a docência. Também aos demais "mestres" que instig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…2012),Cazarotti-Pacheco (2012, 2014, 2016, that originated the clinical categories (and the consequent follow-ups), evidencing, therefore, the existence of the linguistic-cognitive variations functioning among subjects and the inadequacy of the attempt to make subjects fit into a predetermined model(Novaes-Pinto, 2012;Boccato, 2018).Furthermore, there are several occurrences in which the same subject shows significant linguisticcognitive changes, depending on factors such as medication, stress exposure and sleep quality, bringing to light intra-individual variations (Novaes-Pinto, 2012). Therefore, we observed that linguistic-cognitive functioning exceeds the correlation limits between the expected specific and isolated brain area function (predicted in a normality context created from an average brain model) and what is actually found in the daily and real aphasia manifestations.In this way, it becomes possible to glimpse and investigate how subjective, social, historical and cultural aspects influence the meaning different ways and reorganization that each subject constructs, together with the researcher, to deal with his/her aphasia, besides the conception of hypotheses about the linguistic-cognitive phenomena from singular cases detailed examination.…”
mentioning
confidence: 99%
“…2012),Cazarotti-Pacheco (2012, 2014, 2016, that originated the clinical categories (and the consequent follow-ups), evidencing, therefore, the existence of the linguistic-cognitive variations functioning among subjects and the inadequacy of the attempt to make subjects fit into a predetermined model(Novaes-Pinto, 2012;Boccato, 2018).Furthermore, there are several occurrences in which the same subject shows significant linguisticcognitive changes, depending on factors such as medication, stress exposure and sleep quality, bringing to light intra-individual variations (Novaes-Pinto, 2012). Therefore, we observed that linguistic-cognitive functioning exceeds the correlation limits between the expected specific and isolated brain area function (predicted in a normality context created from an average brain model) and what is actually found in the daily and real aphasia manifestations.In this way, it becomes possible to glimpse and investigate how subjective, social, historical and cultural aspects influence the meaning different ways and reorganization that each subject constructs, together with the researcher, to deal with his/her aphasia, besides the conception of hypotheses about the linguistic-cognitive phenomena from singular cases detailed examination.…”
mentioning
confidence: 99%